Proteases: Essential Actors in Processing Antigens and Intracellular Toll-Like Receptors - Manoury, Bénédicte (Frontiers in Immunology, 2013)
MHC class II molecules expressed by professional antigen presenting cells (pAPCs) such as macrophages, B cells and dendritic cells (DCs) play a fundamental role in presenting peptides to CD4+ T cells. However, to elicit CD4+-T cells immunity, pAPCs need an additional signal, which can be delivered by Toll-like receptors (TLRs) molecules. TLRs recognize microbial patterns and are critical in initiating immune responses. Proteases, which provide peptide ligands for the MHC class II antigenic presentation pathway, were recently shown to cleave and activate intracellular Toll-like receptors in endosomal compartments. Here, I give an overview on the individual roles of the most well studied proteases in both antigen and TLRs processing.